SISTEM INFORMASI PENJURUSAN DI SMA XYZ - Andaru, Lina Tri (Jurnal Ilmiah SINUS, 2016)
Majoring is one of determination of students to select their interest according to the enthusiasm, talent and score in SMA XYZ. To do majoring it is required to support from the side of student, class sponsor and guidance and counseling advice. Recently, majoring in SMA still has not been computerized that can be used to support management to make his decision to classify the students according to their majoring. Purpose of this paper is to design and to create its prototype program for majoring information Systemin SMA XYZ. For gaining that purpose to create the majoring information System, it is needed accurate data that can be gathering using interview and literature study methods. The program was developed using mozilla firefox to run the application, Appserv to management the database and Macromedia Dreamwaver 8 to be the text editor and to create the script design. It was concluded that the design and implementation of the majoring information System in SMA XYZ, has already been developed. Keywords : Information System, Majoring, SMA